PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PT ENCAR DAIHATSU BATURAJA - Dadang Kurnia; Sheli Novriyanti; Epriyanti Epriyanti (Jurnal Manajemen Bisnis Unbara, 2023)
The aim of this study was to determine the influence of work environment and workload on employees’ loyalty at PT Encar Daihatsu Baturaja, with a sample size of 32. The analysis method used was quantitative.The calculated t-value for work environment (X1) was 4.739, with a t-table value of 2.045. As the calculated t-value (4.739) was greater than the t-table value (2.045), the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. This indicated a significant influence of work environment on employees’ loyalty. Similarly, the calculated t-value for workload (X2) was 4.203, with a t-table value of 2.045. Since the calculated t-value (4.203) was greater than the t-table value (2.045), the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. This suggested a significant influence of workload on employees’ loyalty.The calculated F-value was 164.131. This value was compared to the F-table value at a confidence level of 95% or α = 5%, which was 3.33. As the calculated F-value (164.131) was greater than the F-table value (3.33), the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted.The coefficient of determination (R-square) in this study was 0.919, indicating that 91.9% of employees’ loyalty (Y) at Encar Daihatsu Baturaja Branch was influenced by the work environment (X1) and workload (X2), while the remaining 8.1% was influenced by other factors not examined in this study, such as innovation and employees’ performance (Chaerudin, et al., 2020:129).